Klimat i system organizacji żłobka a poczucie własnej skuteczności opiekunów dzieci do lat trzech - Krystyna Heland-Kurzak (Problemy Wczesnej Edukacji)
Research about self-efficacy of caregivers of children up to 3 years of age and the climate and organization system of the facility were carried out in all public nurseries in Warsaw. Two hundred twenty four childcare worker in nurseries participated in the study. The study showed that the climate correlated with the influence of the childcare worker’s self-efficacy, while no such relationship with age, work experience or education was observed. Self-efficacy was seen as connected with the atmosphere created in the nursery and positively correlated with it. This relationship was not found in relation to age, experience, or education.